Studi Tentang Siswa Yang Memiliki Sikap Narsisme Dan Penagananya Melalui Latihan Bertanggun Jawab Dalam Konseling Gestal - Rudi, Rudi (JURKAM: Jurnal Konseling Andi Matappa, 2017)
This study aims to determine, factors cause narcissism in SMP Negeri 1Pangkajene, And the implementation of the exercise responsible for solving the problem of student narcissism SMP Negeri 1 Pangkajene,  To find out how the implementation of the training is responsible for solving the problem of student narcissism SMP Negeri 1 Pangkajene. This research is qualitative research with Case Study study type. Technique of collecting data of this research is Observation (Observation), Interview (Interview), Documentation. Subjects in this case study study were determined by purposive are students who experience isolated problems caused by the narcissistic nature of the CNS. The results show that (1) Narcissistic forms experienced by the CNS can be seen by not being able to accept suggestions from others when they are unfavorable (egoism), often uttering offensive sentences (sadism), not caring about others Ignorant), often ruling others (curiosity), have their own assemblies that often gather with people who often give praise.